Adolescent-onset cannabis use and parenting young children: an investigation of differential effectiveness of a digital parenting intervention - Hails, Katherine A.; McWhirter, Anna Cecilia; Sileci, Audrey C. B.; Stormshak, Elizabeth A. (Frontiers in Child and Adolescent Psychiatry, 2024)
There is scant empirical work on associations between current and past cannabis use in parents of young children. As recreational cannabis use is now legal in nearly half of states in the U.S., cannabis use is becoming more ubiquitous. In the current study, parents of toddler and pre-school age children were randomly assigned to participate in an app-based parenting skills program that included telehealth coaching (Family Check-Up Online; FCU-O), with a focus on parenting in the context of substance use. We aimed to test associations between adolescent-onset and current cannabis use and parent mental health and parenting skills, as well as whether effects of the FCU-O on parent mental health outcomes varied as a function of past cannabis use. Participants were 346 parents of children ages 1.5-5 participating in a randomized controlled trial of the FCU-O. Parents screened into the study if they reported current or past substance misuse or current depressive symptoms. After completing a baseline assessment, parents were randomly assigned to the FCU-O or control group and completed a follow-up assessment 3 months later. Parents retrospectively reported on the age when they initially used substances, as well as their current use. After accounting for current cannabis use, adolescent-onset cannabis use was significantly associated with higher symptoms of anxiety and depression, but not with parenting skills. Adolescent-onset cannabis use was found to significantly moderate the effect of the FCU-O on parents' anxiety symptoms. Specifically, the FCU-O was particularly effective in reducing anxiety symptoms for parents with adolescent-onset regular cannabis use, after accounting for current cannabis use. Adolescent-onset regular cannabis use may be a risk factor for later mental health challenges in parents of children under 5. An app-based parenting intervention may be particularly helpful in reducing symptoms of anxiety for parents who used cannabis regularly as adolescents. The findings have significant implications for the prevention of multigenerational risk for substance use and mental health challenges.